The Posting of Workers in the EU at a Glance: A Multidisciplinary Introduction - Frederic De Wispelaere (CESifo Forum, 2022)
Cross-border labor mobility in the EU does not only cover 'permanent' labor mobility but also all types of "temporary" labor mobility such as business trips, seasonal work and posting of workers. The latter concerns non-resident foreign workers whose employment relation is with a non-resident entity, so-called "posted workers". There is a strong link between the export and import of services and the use of intra-EU posting as the former may require the physical presence of workers. Western European countries seem to have a rather dual relationship with the use of intra-EU posting: it is often considered a "Trojan horse" while its use has increased significantly. Moreover, the almost exclusive focus by both scholars and politicians on risks of "social dumping" in labor-intensive sectors may have influenced public perception and acceptance of this type of labor mobility among Member States. Above reality shows that further efforts should be made to map out the number, characteristics, and impact of intra-EU posting. Empirical evidence may refute or confirm existing perceptions and may support evidence-based policy both at national and European level. This specific issue on posted workers zooms in on a number of Member States (Germany, Austria, France, Belgium and Slovenia), often with a focus on a specific sector (e.g., the German meat industry, the Belgian construction sector) or phenomenon (e.g., posted third-country nationals). The first article briefly introduces the social security and labor rules applicable to posted workers and describes the main trends and economic consequences of intra-EU posting. The last article argues that labor mobility by the provision of cross-border services also needs to be taken into account when calculating the employment of a country.
Keywords: 330